2021
DOI: 10.1177/1352458521989090
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory adiponectin in pediatric-onset multiple sclerosis

Abstract: Background: Being obese is associated with both increased risk of developing multiple sclerosis (MS) and greater MS disease activity. Objectives: The objective of this study is to investigate levels and potential pathophysiologic contribution of serum adipose-hormones (adipokines) in pediatric-onset MS. Methods: Following a Luminex adipokine screen, adiponectin (APN) and its isoforms were quantified by enzyme-linked immunosorbent assay (ELISA) in 169 children with incident acquired demyelinating syndromes (ADS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 41 publications
(64 reference statements)
0
14
0
Order By: Relevance
“…( 91 ). The adiponectin hormone secreted by adipose tissue was found to be significantly abundant within the serum of children with MS (n=43, p<0.005) and appears to induce pro-inflammatory states of CD14 + monocytes through increased expression of CD80, CD86, TNF-α and IL-6, as well as the adaptive immune cells IFN-γ producing CD4 + and CD8 + T cells directly or via myeloid cells, and altering the quiescence profile of human microglia ( 92 ). Furthermore, adiponectin levels in the CSF and serum of MS patients appear to correlate with MS disease severity and progression and are higher compared to controls ( 93 96 ).…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 99%
“…( 91 ). The adiponectin hormone secreted by adipose tissue was found to be significantly abundant within the serum of children with MS (n=43, p<0.005) and appears to induce pro-inflammatory states of CD14 + monocytes through increased expression of CD80, CD86, TNF-α and IL-6, as well as the adaptive immune cells IFN-γ producing CD4 + and CD8 + T cells directly or via myeloid cells, and altering the quiescence profile of human microglia ( 92 ). Furthermore, adiponectin levels in the CSF and serum of MS patients appear to correlate with MS disease severity and progression and are higher compared to controls ( 93 96 ).…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 99%
“…A recent study comparing 33 children with MS to 54 children with MOGAD, and 29 healthy controls, observed significantly higher levels of adiponectin in the serum of MS patients compared to both the MOGAD and healthy control patients (p = 0.02) (59). This study also investigated the functional consequence of elevated adiponectin on immune cells and discovered that adiponectin from the serum of pediatric MS patients led to pro-inflammatory responses in CD14+ monocytes, T-cell activation, upregulation of CNS microglia proinflammatory markers, and downregulation of CNS microglial specific quiescent/anti-inflammatory markers (63) all evidence supporting a role of adiponectin to induce disease in children with MS. Finally, there has been evidence suggesting that obesity, through disruption of TH17/Treg balance, may alter the gut microbiome resulting in dysregulation of the intestinal immune response (65).…”
Section: Environmental Risk Factors: the Role Of Obesitymentioning
confidence: 71%
“…Obesity has also been associated with IL-6 dependent TH17 production which has been shown to exacerbate EAE in mice (62). Another adipokine, adiponectin, has also been implicated in the pathogenesis of MS (63). One study found elevated levels of leptin and fatty acid binding protein-4 as well as reduced adiponectin in boys and girls with MS compared to age and sex-matched controls (64).…”
Section: Environmental Risk Factors: the Role Of Obesitymentioning
confidence: 99%
“…Moreover, serum from POMS patients induced an adiponectin-driven pro-inflammatory response characterized by activation of CD4 and CD8 T cells as well as reduced microglial senescence. 30 POMS risk is also increased by exposure to secondhand smoke during childhood. 31 In adults with MS, smoking has also been linked to worse outcomes, including greater disability.…”
Section: Ms Is One Disease Across the Age Spanmentioning
confidence: 99%
“…Moreover, serum from POMS patients induced an adiponectin-driven pro-inflammatory response characterized by activation of CD4 and CD8 T cells as well as reduced microglial senescence. 30…”
Section: Ms Is One Disease Across the Age Spanmentioning
confidence: 99%